PENGARUH PENERAPAN MEDIA KONKRET PADA MATA PELAJARAN MATEMATIKA MATERI PENJUMLAHAN TERHADAP HASIL BELAJAR SISWA KELAS I MI AN-NIDHOM KEBUNREJO GENTENG - Ramiati, Eka; Mashuri, Imam; Wariyani, Dewi (PGMI Department of Institut Agama Islam Ibrahimy Genteng Banyuwangi, Indonesia, 2022)
This research aims to determine the influence of the application of concrete media on the subjects of mathematics of summation materials on the learning outcomes of mi class I students An-Nidhom Kebunrejo Genteng. This type of research is quantitative with experimental methods with pre-experimental research design one group pretest-posttest. The research population is the entire mi An-Nidhom student of the 2018/2019 school year which amounts to 167 students. While the sample used in this study was 34 students in class I. Research data is collected through tests and documentation. The results showed that there was an influence on the application of concrete media on the mathematics subjects of summing materials on the learning outcomes of mi class I students An-Nidhom Kebunrejo Genteng. This is based on the results of general hypothesis testing obtained t count greater than t table which is 11,109 > 2,037 with a significant level smaller than 0.05 which is 0.00. Thus it can be concluded that there is an influence on the application of concrete media on the subjects of mathematics summing materials on the learning outcomes of class I MI An-Nidhom Kebunrejo Genteng students. Where students after getting the application of peer media in mathematics subjects of summation materials experienced an increase in learning outcomes seen from the postest results given after treatment in class. The results of this study can be used as a reference by the school to conduct a follow-up program to overcome problems in classroom learning, especially related to learning outcomes.